Representasi nilai budaya Islami dalam Iklan Sari Ayu “Hijab” - Arfriani Maifizar; rahma husna yana (Jurnal Community, 2019)
The achievement of the advancement of cultural globalization has spread to various advertisements in the mass media including one of Sari Ayu Ads. The transformation of Islamic culture has made one of the important changes in the representation of cultural values in advertising. The focus of this study examines the Islamic cultural values represented by ad text and how Islamic cultural values are represented through ad text. The approach used in understanding signs was developed by Roland Barthes. Roland Barthes interpreted the denotation and connotation of the Sari Ayu ad text sample. The results found that the cultural values represented in Sari Ayu's ad text indicate the value of harmony to nature, traditional beauty care values, modern cultural values, gender, social class, tradition, femininity, and history. The Islamic values contained in Sari Ayu Ads represent Indonesia in interpreting universal cultural values for the development of the world today. These cultural values are widely presented, especially seen in modern cultural values mixed with Islamic values in text and visual advertisements.